Optimalisasi Perancangan Chassis Mobil Listrik Tipe Prototype Menggunakan Autodeks Inventor - Fredyansah, Muhamad; Gunawan, Yuspian; Sisworo, Raden Rinova (Teknik Mesin Universitas Halu Oleo, 2022)
Prototype cars are future vehicles with special designs that maximize efficiency. An important part of the vehicle, one of which is the chassis, which functions to support the passengers, engine, body and the weight of the chassis itself, so it is necessary to design a lightweight and strong chassis. The purpose of this research is to determine and study the stress, strain, displacement and safety factors that occur in the prototype type electric car chassis designed. 3-dimensional design modeling and simulations were performed on Autodesk Inventor software. Based on the simulation results of loading 60kg, the optimal material is aluminum 6061 compared to aluminum 6063 with the results obtained for stress, strain, displacement, and safety factor. on aluminum 6061 with successive values of 59.712 MPa, 0.000796, 1.299 mm, 4.605. While the aluminum 6063 with a value of 59.628 MPa, 0.000806, 1.316 mm, 3.585. The greater the load, the greater the stress and strain.Key words: Chassis, Desingn, Prototype, Simulation